Bo the brave - Elliott, Rebecca (2020)
In order to earn their Bravery Patches, Bo and the other unicorns of Sparklegrove Forest have to camp out in the forest for three nights; but the night is full of frightening noises, and when a misunderstanding offends some pixies, the unicorns resolve to face their fears and confront the "monsters" who are stealing the pixies' houses.
Keywords: Unicorns -- Juvenile fiction; Magic -- Juvenile fiction; Courage -- Juvenile fiction; Camping -- Juvenile fiction; Pixies -- Juvenile fiction; Unicorns -- Fiction; Magic -- Fiction; Courage -- Fiction; Fear of the dark -- Fiction; Camping -- Fiction; Pixies -- Fiction